PRESTASI BELAJAR SEBAGAI DAMPAK DARI MINAT BACA DAN BIMBINGAN BELAJAR SISWA IPS - Kartika Mariskhana (Universitas Bina Sarana Informatika, 2019)
This research aims to determine how much the impact of interest in reading and tutoring on learning achievement by social science students in junior high school Jakarta 1. In this research, the authors distributed questionnaires to students of 9 grade subjects of social science in junior high school Jakarta 1. The survey method used in this research is random sampling and calculates the result of questionnaires that have been filled by students using the slovin formula, where there are a population of 124 students consisting of 68 men and 56 woman.from the total population, a sample of 95 students from junior high school Jakarta 1 were taken who attended the tutoring program. Keywords: interest in reading, tutoring, learning achievement